2015
DOI: 10.1177/1359105315580214
|View full text |Cite
|
Sign up to set email alerts
|

Normal-weight and overweight female adolescents with and without extreme weight-control behaviours: Emotional distress and body image concerns

Abstract: The objective of this study was to analyse emotional distress and concerns related to body image in 712 normal-weight and overweight adolescent girls. A total of 12.3 per cent of the normal-weight girls and 25 per cent of the overweight girls showed extreme weight-control behaviours. In normal-weight adolescents, their engagement in extreme weight-control behaviours was associated with high levels of somatic symptoms, a drive for thinness and control over eating. In overweight girls, high levels of drive for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 44 publications
5
25
0
3
Order By: Relevance
“…En consonancia con estudios previos, las adolescentes con mayor IMC presentaban una mayor insatisfacción corporal (31) y un mayor número de conductas de control del peso (3)(4)(5)(6)(7)14). Sin embargo, no se encontró relación entre el IMC y los niveles de ansiedad y depresión.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En consonancia con estudios previos, las adolescentes con mayor IMC presentaban una mayor insatisfacción corporal (31) y un mayor número de conductas de control del peso (3)(4)(5)(6)(7)14). Sin embargo, no se encontró relación entre el IMC y los niveles de ansiedad y depresión.…”
Section: Discussionunclassified
“…Más allá de su relación con los trastornos de la alimentación (11,12), la obesidad frecuentemente coexiste con otras patologías, entre las que destacan la depresión (12,13) y la ansiedad (14)(15)(16)(17). No obstante, hay estudios que no apoyan la asociación entre un alto índice de masa corporal y problemas de salud mental (18)(19)(20), ni la comorbilidad entre la obesidad y la ansiedad y la depresión (21).…”
Section: Introductionunclassified
“…Cruz-Sáez et al (2015) found 12.3 per cent of normal-weight girls and 22.5 per cent of overweight girls with extreme weight-control behaviours (EWCBs), that is, self-induced vomiting, taking laxatives, diuretics, diet pills and fasting. In normal-weight adolescents, engagement in EWCBs was associated with high levels of somatic symptoms, a drive for thinness and control overeating.…”
Section: Theory Of Obesitymentioning
confidence: 99%
“…These results led the authors to conclude

emotional distress, excessive importance placed on physical appearance to define oneself, low self-esteem and the negative cognitions associated with the body and eating, play an important role in the development of weight-control behaviours that put adolescent girls’ health at risk, even those considered normal-weight. (Cruz-Sáez et al, 2015)

…”
Section: Theory Of Obesitymentioning
confidence: 99%
“…El presente estudio trató de analizar la asociación entre el IMC, la insatisfacción corporal, el nivel de ansiedad y depresión y las conductas de control del peso en una muestra de chicas adolescentes con sobrepeso/obesidad. En consonancia con estudios previos, las adolescentes con mayor IMC presentaban una mayor insatisfacción corporal (31) y un mayor número de conductas de control del peso (3)(4)(5)(6)(7)14). Sin embargo, no se encontró relación entre el IMC y los niveles de ansiedad y depresión.…”
Section: Discussionunclassified